Friction Stir Welding and Processing VIII - Mishra, Rajiv; Mahoney, Murray; Sato, Yutaka; Hovanski, Yuri (The Minerals, Metals & Materials Series,, 2016)
This collection focuses on all aspects of science and technology related to friction stir welding and processing.